2014
DOI: 10.1021/nn502125h
|View full text |Cite
|
Sign up to set email alerts
|

Precise Engineering of siRNA Delivery Vehicles to Tumors Using Polyion Complexes and Gold Nanoparticles

Abstract: For systemic delivery of siRNA to solid tumors, a size-regulated and reversibly stabilized nanoarchitecture was constructed by using a 20 kDa siRNA-loaded unimer polyion complex (uPIC) and 20 nm gold nanoparticle (AuNP). The uPIC was selectively prepared by charge-matched polyionic complexation of a poly(ethylene glycol)-b-poly(L-lysine) (PEG-PLL) copolymer bearing ∼40 positive charges (and thiol group at the ω-end) with a single siRNA bearing 40 negative charges. The thiol group at the ω-end of PEG-PLL furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(112 citation statements)
references
References 35 publications
0
112
0
Order By: Relevance
“…It has been demonstrated that particle size has a substantial impact on the pharmacokinetics and biodistribution of nanoparticles. Some studies have pointed out that nanoparticles ,50 nm may penetrate into deeper tissue 34,35 because larger particles may have poor delivery to less leaky sites in highly heterogeneous tumor tissues 36 and narrow spacing between tumor cells. 37,38 The diameter of a poly (amido amine) generation 5.0 (PAMAM G5) dendrimer used in our study is about 5.4 nm.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that particle size has a substantial impact on the pharmacokinetics and biodistribution of nanoparticles. Some studies have pointed out that nanoparticles ,50 nm may penetrate into deeper tissue 34,35 because larger particles may have poor delivery to less leaky sites in highly heterogeneous tumor tissues 36 and narrow spacing between tumor cells. 37,38 The diameter of a poly (amido amine) generation 5.0 (PAMAM G5) dendrimer used in our study is about 5.4 nm.…”
Section: Discussionmentioning
confidence: 99%
“…As inorganic nanoparticles display numerous advantages in drug delivery for the treatment of diseases, several inorganic nanocarriers have been created for targeted treatment [99][100][101][102][103]. These approaches are limited by certain factors, however, such as toxicity and lack of biodegradability [12].…”
Section: Drug Deliverymentioning
confidence: 99%
“…35 The formation of a stable uPIC structure from dsRNA is used to construct a palisade of block ionomers to pair with dsRNA (small interfering RNA) onto gold nanoparticles to create systemically injectable nanocarriers to deliver small interfering RNA therapeutics to target organs to treat cancer. 36,37 …”
Section: Unit Pics and Micellesmentioning
confidence: 99%